Pelaksanaan peraturan tentang legalitas para pengobat tradisional komplementer berdasarkan Undang-Undang Kesehatan No. 36 Tahun 2009 - Juliana Juliana; I Gede Agus Kurniawan (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
This research aims to analyze the implementation of legality regulations for Traditional Complementary Healers (TCH) based on Health Law No. 36 of 2009. The study focuses on Denpasar, with an emphasis on acupuncture and muscle massage practices. Using a qualitative approach, this study identifies that a majority of TCHs in Denpasar (around 90%) have not yet complied with the legality requirements set by Health Law No. 36 of 2009. Factors influencing the fulfillment of legality encompass legislative aspects that lack specificity in regulating traditional healing, limited attention from law enforcement, as well as challenges in infrastructure and insufficient support from professional organizations and local authorities. Society tends to deprioritize legality when choosing TCHs due to the deep-rooted cultural belief in traditional healing methods. This research underscores the need for stronger guidance and supervision from Local Governments to assist TCHs in meeting legality prerequisites. In conclusion, the implementation of legality regulations for TCHs based on Health Law No. 36 of 2009 in Denpasar still encounters significant challenges involving various factors, including culture and inadequate regulations.